Endoscopic-assisted transorbital surgery: Where do we stand on the scott’s parabola? personal considerations after a 10-year experience - Iacopo Dallan; Lodovica Cristofani-Mencacci; Giacomo Fiacchini; Mario Turri-Zanoni; Wouter van Furth; Matteo de Notaris; Miriana Picariello; Enrico Alexandre; Christos Georgalas; Luca Bruschini (Frontiers in Oncology, 2022)
Transorbital approaches are genuinely versatile surgical routes which show interesting potentials in skull base surgery. Given their “new” trajectory, they can be a very useful adjunct to traditional routes, even being a valid alternative to them in some cases, and add valuable opportunities in selected patients. Indications are constantly expanding, and currently include selected intraorbital, skull base and even intra-axial lesions, both benign and malignant. Given their relatively recent development and thus unfamiliarity among the skull base community, achieving adequate proficiency needs not only a personalized training and knowledge but also, above all, an adequate case volume and a dedicated setting. Current, but mostly future, applications should be selected by genetic, omics and biological features and applied in the context of a truly multidisciplinary environment.